Compensation Award for Wrongful Dismissal of Pregnant Women in Israel - Yael Ilany, Yael Ilany (Studia Edukacyjne, 2020)
The employment issues relating to women in the workplace, including the employment and dismissal rights of women and in particular the dismissal of pregnant women, are important topics in the Israeli conversation on the equality of women in the workplace. The dismissal of pregnant women in Israel is deemed to be a wrongful dismissal and is a frequent topic of claims submitted to the Israeli Labor Court. Consequently, the subject is of major interest to Israeli employers and employees. This article presents a review of empirical legal research and analysis of Israeli Labor Court rulings of compensation awards for wrongful dismissal of pregnant women. The objective of the research is to reveal the factors influencing compensation awards by the court and to indicate tendencies apparent in court assessment of compensation.